STUDI CEMARAN MIKROBA PADA RENDANG SAPI DI RUMAH MAKAN PADANG DI KECAMATAN KUTA, KABUPATEN BADUNG, BALI - Sembiring, Sixtian Brema; Putra, I Nengah Kencana; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
The purpose of this study was to determine the microbial contamination on beef rendang and hygiene sanitation practices at Padang restaurant in Kuta sub district, Badung regency , Bali. This study used survey method with purposive sampling technique. The sampling determination was conducted at several Padang restaurants in Kuta sub district , Badung regency, Bali . The data obtained were presented in the form of tables, pictures, and analyzed descriptively. The variable observed were total microbes, Escherichia coli, and Staphylococcous aureus. The results showed that 90% of beef rendang was suitable with requirements of total microbes for processed meat in Indonesia ( SNI< 5 x 10 5 ), 80% of beef rendang was suitable with requirements of Escherichia coli for processed meat in Indonesia and 100% of beef rendang was suitable with requirements of Staphylococcous aureus for processed meat in Indonesia. The amount of 90% of beef rendang was cooked in the morning, 20% of rendang was served over 24 hours. The hygiene and sanitation practices at Padang restaurant in Kuta subdistrict, Badung regency were good enough .